Fostering Environmental Care Attitudes through the Implementation of the Science-Technology-Society Learning Model in Elementary Schools - Gerald Amatre; Huang Jiln; Pradeepan K Sarma (Journal of Academic Biology and Biology Education, 2026)
Purpose of the study: This study investigated the implementation of the Science-Technology-Society learning model and its effectiveness in improving environmental care attitudes among elementary school students through contextual learning activities that integrate scientific concepts, technological developments, and environmental issues relevant to daily life. Methodology: A Classroom Action Research design based on the Kemmis and McTaggart model was employed, involving planning, action, observation, and reflection stages conducted over three cycles. The participants were 23 elementary school students in Kampala District, Uganda. Data were collected using environmental care attitude observation sheets and Likert-scale questionnaires. Quantitative data were analyzed using descriptive statistics and percentage calculations, while qualitative data were examined through the interactive analysis model of Miles and Huberman. Main Findings: The results showed a continuous improvement in students’ environmental care attitudes throughout the intervention. Achievement levels increased from 69.28% in the pre-intervention stage to 77.79% in Cycle I, 79.71% in Cycle II, and 85.94% in Cycle III. Students demonstrated greater responsibility for maintaining environmental cleanliness, managing waste, caring for plants, and practicing environmentally responsible behavior in both learning activities and daily school routines. Novelty/Originality of this study: This study contributes to environmental education research by identifying how the implementation stages of the Science-Technology-Society learning model foster environmental care attitudes among elementary school students. The findings provide evidence that contextual science learning can effectively promote environmental awareness and support sustainability education, contributing to the achievement of Sustainable Development Goals through character development at the primary education level.